2021
DOI: 10.1093/cercor/bhab038
|View full text |Cite
|
Sign up to set email alerts
|

Drifts in Prefrontal and Parietal Neuronal Activity Influence Working Memory Judgments

Abstract: The dorsolateral prefrontal cortex (dlPFC) plays a critical role in spatial working memory and its activity predicts behavioral responses in delayed response tasks. Here, we addressed if this predictive ability extends to other working memory tasks and if it is present in other brain areas. We trained monkeys to remember the location of a stimulus and determine whether a second stimulus appeared at the same location or not. Neurophysiological recordings were performed in the dorsolateral prefrontal cortex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Our study revealed that NMS is more prevalent among dorsolateral prefrontal than posterior parietal neurons in the MSNG task, in which activity from both areas has been shown to influence spatial working memory behavior ( Li et al, 2021 ). NMS was greater in the PFC, even after controlling for the higher overall selectivity for stimulus variables that was present in our prefrontal sample.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our study revealed that NMS is more prevalent among dorsolateral prefrontal than posterior parietal neurons in the MSNG task, in which activity from both areas has been shown to influence spatial working memory behavior ( Li et al, 2021 ). NMS was greater in the PFC, even after controlling for the higher overall selectivity for stimulus variables that was present in our prefrontal sample.…”
Section: Discussionmentioning
confidence: 77%
“…The mixed selectivity of a specific neuron could be defined in different ways, depending on what task variables were under examination. Both PFC and PPC show location selectivity in a spatial working memory task, during the stimuli presentation and the delay period ( Li et al, 2021 ). We thus considered whether such selectivity may constitute another form of NMS, and we wanted to know how many cells maintained spatial selectivity in different task epochs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers assumed the existence of an asymmetric relationship between WM and decision-making, that is, impaired IGT performance does not obligatory rely on WM, but impaired WM leads to poor IGT performance (Bagneux et al, 2013). This was also supported by the effects of dorsolateral prefrontal cortex lesions, a human brain region critically involved in WM (Li et al, 2021;Petrides, 2000, Funahashi, 2006Goldman-Rakic, 1996;Fuster and Alexander, 1971), and imaging studies (Ernst et al, 2002;Li et al, 2010). It suggests the existence of distinct decision mechanisms within the prefrontal cortex as well as executive functioning (Bechara and Martin, 2004).…”
Section: Discussion (Inter and Intra Strains)mentioning
confidence: 99%
“…To successfully perform the task, monkeys had to continuously update an internal estimate of the relative target location (the latent state) by integrating their own movement velocity inferred from the sparse optic flow cues. Brain regions in the posterior parietal cortex (PPC) have been implicated in various aspects of this computation such as optic flow processing 17 , 18 , working memory 19 21 , as well as planning of spatial movements 22 , 23 . Because we are primarily interested in understanding the mechanisms of latent state computation rather than optic flow processing per se, we wanted to record neural activity in a region within PPC that likely already receives abstract velocity signals, such that it may serve as the locus of latent state computation in our task.…”
Section: Introductionmentioning
confidence: 99%